2018
DOI: 10.4238/gmr18066
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Selection of resistance sources to common bean anthracnose by field phenotyping and DNA marker-assisted screening

Abstract: The main goal of this work was to select resistance sources to common bean anthracnose by field phenotyping and DNA marker-assisted screening. Fifty-five common bean genotypes, including differential varieties, characterized resistance sources, elite lines, cultivars and controls, were evaluated in a field inoculation trial and screened with SCAR markers linked to resistance genes that are important in Brazil. The field trial was carried out in Santo Antônio de Goiás, GO, Brazil, during the fall/winter growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…3 ) and G2333 (Co-4 2 ) No 8 and12 respectively. This is in agreement with Vieira et al (2018) who did similar work in Brazil. The marker however, did not detect the possible gene for resistance among the French bean genotypes used in this study.…”
Section: Molecular Markers Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…3 ) and G2333 (Co-4 2 ) No 8 and12 respectively. This is in agreement with Vieira et al (2018) who did similar work in Brazil. The marker however, did not detect the possible gene for resistance among the French bean genotypes used in this study.…”
Section: Molecular Markers Analysissupporting
confidence: 93%
“…Race 65 may be considered as widespread as it was identified in Kakamega and Mwea. Races 65 and 73 have also been documented to be prevalent in Brazil (Vieira et al, 2018). Furthermore, race zero (0) was also identified in the present study as it could not infect any of the twelve anthracnose differential cultivars as previously reported in Kenya (Mogita et al, 2011b) and Uganda (Nkalubo, 2006).…”
Section: Physiological Characterization Of C Lindemuthianumsupporting
confidence: 83%
“…For this reason, anthracnose resistance in BRSMG Realce should be considered as a major gene or complex gene locus for breeding. It was also verified that Co-Realce segregates independently from Co-3 ( Table 1 ), the physically closest anthracnose resistance locus on Pv04 that has already been used by the Embrapa common bean breeding program to develop elite germplasm ( Vieira et al., 2018 ). Still considering physical map evidences, the positions of Co-3 (1,286,490 bp) ( Murube et al., 2019 ), Co-15 (9,432,376 bp) ( Sousa et al., 2015 ) and Co-16 (1,537,169 bp) ( Coimbra-Gonçalves et al., 2016 ) on Pv04 shown that those anthracnose resistance loci are distant from Co-Realce by 780,839 bp, 8,926,725 bp and 1,031,518 bp, respectively ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 76%
“…In the present study, four SNP markers associated with the anthracnose-resistant locus were analyzed. In case of the markers snpPV0068 (G:C) and snpPV0070 (G:T), the "G" alleles (of both SNPs) were identi ed in the G-2333, SEL 1308, PI 207262, K-10, K-13, and CNFC 5547 lines (Table S6), which are known sources of the resistant allele of Co-4 2 (Kelly and Vallejo 2004;Vieira et al 2018). Another 22 black grain lines also displayed this same allele (Table S6).…”
Section: Snp Markers Associated With the Co-4 And Co-u Locimentioning
confidence: 99%
“…Portilla et al (2021) when evaluating the Co-4 marker snpPV0069 (closely linked to the snpPV0068 and snpPV0070), developed from G2333 genotype (Lobaton et al 2018) and available at HTPG portfolio, did not identify any signi cant effect of association, which was suggestive of a race speci c resistance gene interaction. The Co-4 2 is a dominant allele of the Co-4 locus and has been used by breeding programs worldwide (Kelly and Vallejo 2004;Vieira et al 2018) due to its broad spectrum of resistance to several C. lindemuthianum pathotypes (Balardin and Kelly 1998;Silvério et al 2002).…”
Section: Snp Markers Associated With the Co-4 And Co-u Locimentioning
confidence: 99%